Resistência à corrosão e à tribocorrosão de aços inoxidáveis supermartensíticos utilizados na indústria de petróleo e gás - Renata Braga Soares (2016)
Supermartensitic stainless steels have recently been introduced in the oil and gas industries to substitute more expensive duplex stainless steels for onshore and offshore tubing applications. This work aimed at evaluating the corrosion and tribocorrosion behavior of supermartensitic steels for application in oil and gas industry in aqueous media containing chlorides. The steel microstructure was characterized using optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), interferometry, X-ray diffraction (XRD), Mössbauer and electron backscattered diffraction (EBSD). The electrochemical characterization on steel surface supermatensitic stainless steel has been studied using potentiodynamic anodic polarization, cyclic potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), Mott-Schottky and scanning vibrating electrode technique (SVET). A tribocorrosion setup was configured in order to study the triboelectrochemical behavior of a supermartensitic steel. Wear analysis indicated that three-body abrasion was the dominant wear mechanism. Due to the synergetic effect of wear and corrosion, the concentration of pits was higher with rubbing but the pit propagation was inhibited. The smallest abrasive particles promoted the highest pit growth inhibition. The effect of larger diamond particles on tribocorrosion of supermartensitic steel would be less harmful than the effect of smaller abrasive particles. Coarse cuboidal TiN particles were identified on the steel surfaces of all samples. The TiN inclusions showed microvoids and a nucleous containing magnesium, aluminum and calcium oxides. Mössbauer analysis identified 0.7, 0.5 and 0.9% of retained austenite in SMSS samples as-quenched and tempered at 600oC and 640oC, respectively. The sample tempered at 600oC showed the lowest grain size, evaluated by using EBSD technique, and the highest localized corrosion resistance in a saline medium. The SMSS sample tempered at 640oC showed no electrochemical activity after 3600s of immersion in a saline solution by using a SVET technique, but after 86400s, a pit was detected. SVET analysis showed the association of a localized corrosion sites with the TiN inclusion on the steel surface. The 0.6 mol/L NaCl aqueous solution was the less aggressive electrolyte to the supermartensitic stainless steel (SMSS). The SMSS tempered at 600°C exhibited the highest corrosion resistance in two electrolytes. Furthermore, the capacitance study shows that the passive films formed on supermartensitic steel behave as p-type semiconductors below the flat band potential.